Influence of Basin Hydrogeology in the Detectability of Narrow Rivers by Sentinel2-A Satellite Images: A Case Study in Karamenderes (Çanakkale) - Muhittin Karaman; Emre Özelkan; Suat Taşdelen (Doğal Afetler ve Çevre Dergisi)
Since the flow paths of linear water components are generally narrow and containing vegetation, there are some difficulties in the use of satellite images monitoring changes in the linear water components. The aim of this study was to evaluate the detectability of narrow rivers such as Karamendere River of Çanakkale using 10 meters spatial resolution multispectral Sentinel2-A satellite images and to evaluate the effect of hydrometeorological conditions of the basin on the seasonal change in the detected river line. In this study, which was carried out using satellite images of different hydrogeological periods, the modified normalized difference water index (MNDWI) generated from the satellite images was used to determine the water components. According to the satellite image analysis, the existence of the stream was detected as 59% in January, 26% in April and 18% in September on the 102 km long stream line of the Karamenderes River. According to the Thornthwaite water budget, the river bed area which can be determined by satellite images was higher than the water deficient periods in the hydrogeological periods where there was a water surplus caused increase in the water areas in the creek wider than 10 meters. The hydrometeorological cycle, agricultural irrigation, daily water consumption and other human-induced factors were effective on the decreased water flow. In the hydrometeorological cycle, while precipitation and melting snow increase discharge, increased temperature, decreased precipitation and high evapotranspration caused a decrease in flow rate. It was revealed that the selection of the date of satellite images to be used according to the hydro-meteorological characteristics (flow, precipitation, temperature, etc.) of the basin increased the success of determining water components with narrow river bed.